Penerapan Metode RT-BT (Roundtable Berbasis Teks) dalam Pembelajaran Menulis Teks Dialog Berbahasa Jawa Siswa Kelas VIII A2 SMP Islam Sultan Agung 4 Semarang Tahun Ajaran 2021-2022 - Widiyanti, Eka; Alfiah, Alfiah; Sulajari, Bambang (Universitas PGRI Semarang, 2022)
This study aims to describe the results of the application of the RT-BT (Text Based Roundtable) method in learning to write Javanese dialogue texts for class VIII A2 students of Islamic Junior High School Sultan Agung 4 Semarang in the 2021-2022 Academic Year. This is motivated by the lack of interest of students in learning to write Javanese dialogue in class VIII A2. Some of the difficulties experienced by students, including the selection of aspects of word choice or diction, aspects of spelling understanding that are still lacking, aspects of understanding difficult vocabulary, and the use of variations in language have not been understood by students so that there are still errors in its application. In addition, the teaching method that has not been varied is one of the factors causing the students' lack of enthusiasm in the learning process in the classroom. Thus, the formulation of the problem obtained is how the results of applying the RT-BT (Text Based Roundtable) method in learning to write Javanese dialogue texts are.This research is included in experimental research because the data obtained are used to determine the effect of certain treatments on controlled conditions. The approach used is descriptive quantitative because the data obtained is calculated statistically, then the data is analyzed descriptively by describing the results of the calculation of the data. The data obtained in this study were collected by means of observation (observation) and questionnaires (questionnaire), while the sampling used was purposive sampling.After analyzing the data, the following research results were obtained: 1) In the aspect of knowledge, there were 18 students or 72% who scored above the KKM, while 7 students or 28% had not reached the KKM. From this percentage, the completeness value obtained is 74.72. 2) In the aspect of skills, there are 22 students or 88% have reached the KKM specified, while 3 students or 12% have not reached the KKM so that the average value of the class is 82.88. Thus, the application of the RT-BT (Text Based Roundtable) method in learning to write Javanese dialogue texts for class VIII A2 students can have an influence on the achievement of the specified learning objectives.